Relationship Marketing in the Consumer Market: Scientific Production Profile and Research Agenda - Demo, Gisela; Lima, Talita; Scussel, Fernanda; Miranda, Paulo; Moreno, Lucas (Future Studies Research Journal: Trends and Strategies, 2021)
Objective: in view of the relevance of relationship marketing for organizations operating in the business-to-consumer market (B2C) and the gap in the literature regarding the comparison of national and international production scenarios, the objective of this article was to map the state of the art consumer relationship and propose a research agenda Method: a bibliometric review was carried out with 435 articles published between 2015 and 2019, classified according to demographic, institutional and methodological criteria Results: there was a predominance of empirical and quantitative articles, in addition to the need for conceptual development for the theme. There is a preference for the application of research in the private sector, configuring the research gap of the theme with regard to the public sector Conclusions: the contributions reside in the presentation of research itineraries, whose main purpose is to assist the theoretical and empirical development of relationship marketing, benefiting both the academic community and organizations